Investigation of epoxidation of used cooking oils with homogeneous and heterogeneous catalysts. (1st November 2019) - Kurańska, Maria; Beneš, Hynek; Prociak, Aleksander; Trhlíková, Olga; Walterová, Zuzana; Stochlińska, Wioletta
Abstract: A sustainable solvent-free process of the utilization of waste cooking oils has been developed using different types of catalysts. The process offers a tool to create a cleaner technology for the production of bio-components which will be building blocks of the sustainable polymeric materials. Used cooking oils collected from local restaurants have been epoxidized using homogeneous (H2 SO4, H3 PO4 ) and heterogeneous (Amberlite IR-120) catalysts. The epoxidation reactions were carried out using "in situ"-formed peroxy acid. The effect of the catalysts on the epoxidation process and the properties of the final products were described. The highest conversion (81%) was achieved for the reaction catalyzed by H2 SO4, but the selectivity of this reaction was the lowest (47%). On the other hand, the highest selectivity was obtained for the reaction performed using H3 PO4, but the yield of this reaction (26%) was the lowest. In the case of ion-exchange resin (Amberlite IR-120), the conversion of double bonds, selectivity and efficiency were 55, 74 and 40%, respectively. The extent of side reactions depended on the type of used catalyst as it was confirmed by FTIR, GPC, MALDI-TOF as well as by the changes of the product's viscosity. The results should play an important role in the future development of a new approach to the environmentally friendly solvent-free epoxidation process of waste oils.